A new score to validate coma in emergency department — FOUR score - Murthy, TVSP (Indian Journal of Neurotrauma, 2009)
The Glasgow Coma Scale (GCS) is the most widely used method for evaluation of coma, but it has a number of shortcomings, including limited utility in intubated patients and an inability to assess brainstem reflexes. A new coma score, the Full Outline of Un Responsiveness (FOUR) has been developed. to overcome these shortcomings and to provide further neurological details that might predict outcome in coma. Four different components are included in the FOUR score (eye, motor, brainstem and respiration), each of which has a maximal score of 4. In contrast to the GCS, verbal response is not a component of the FOUR score, making it fully applicable in intubated patients.
Keywords: coma; GCS; FOUR score; head injury